2015
DOI: 10.1016/j.apenergy.2014.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for the economic optimisation of energy storage systems for frequency support in wind power plants

Abstract: This paper proposes a methodology for the economic optimisation of the sizing of Energy Storage Systems (ESSs) whilst enhancing the participation of Wind Power Plants (WPP) in network primary frequency control support. A generalised approach was taken for the design of the methodology, so it can be applied to different energy markets and concerning different ESSs. The methodology includes the formulation and solving of a Linear Programming (LP) problem.The methodology was applied to the particular case of a 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(48 citation statements)
references
References 16 publications
0
47
0
Order By: Relevance
“…The work in [15] showed that pumped storage can be also very useful in isolated systems, improving both the dynamic security and the economic operation of the grid. Another example is presented in [16] where the sizing of a battery for a grid connected wind farm in order to provide frequency support is described. Research on storage sizing for renewable energy integration is driven in part by the high capital cost of storage.…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…The work in [15] showed that pumped storage can be also very useful in isolated systems, improving both the dynamic security and the economic operation of the grid. Another example is presented in [16] where the sizing of a battery for a grid connected wind farm in order to provide frequency support is described. Research on storage sizing for renewable energy integration is driven in part by the high capital cost of storage.…”
Section: State Of the Artmentioning
confidence: 99%
“…The resulting time series is scaled as shown in Equation (15) in order to obtain the desired standard deviation σ. The time series is then filtered in order to remove the elements larger than 1 in absolute value as shown in Equation (16).…”
Section: Generation Of the Prediction Errors Time Seriesmentioning
confidence: 99%
“…Vanadium batteries supporting wind power plants to provide PCR are discussed in [29], whereas time shifting is investigated in [30] according to U.K. policy requirements. An installation of 1.6 MW/0.4 MWh Li-ion battery combined with a wind power plant in Denmark providing ancillary services is described in [31].…”
Section: Bess Integration For Supplying Primary Control Reserve (Pcr)mentioning
confidence: 99%
“…Thus, the use of energy storage could be profitable for the operator of a wind power plant that is participating in frequency regulation. It is to be mentioned that the research works presented in [63][64][65] do not suggest a safe margin of wind penetration in order to ensure a satisfactory frequency response in a power system. Expansion of wind generation in different real-world power networks are described in [29,[66][67][68][69].…”
Section: Maximum Wind Penetration Levelmentioning
confidence: 99%
“…For instance, hourly analyses of electricity supply and demand of New York State are performed using a deterministic model in [64] to show that adaptation of a heat pump could be beneficial to increasing the utilisation of wind power. On the other hand, energy storage systems are deployed in [65] to enhance the participation of wind power plants in primary frequency regulation. It is found that energy storage can provide power reserves.…”
Section: Maximum Wind Penetration Levelmentioning
confidence: 99%